(3ehdO SjO GdChdjf hGdBNQjf hMHjH hNdjd QH GdYGdejfs - (3HMQb, eMeO Hf YeQ Hf eHGQc, J(B930(3g`s
(3ChdgG (B:s
(3GdMeO ddg HGQF CeTGL GdfSe haGJb QJGL Gdcee hehdL GdCfhGQ aj GdXde heNQL GdehLhOGJ ef GdYOes
(3BNQgG (B:s
(3hGLYd BNQ cdGefG dG Edg EdG Gddg eMeO QShd Gddg hCfJ MSHfG hfYe Gdhcjd SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 315s
(3eYLe GdeDdajf(B: 3 / 564s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs